Cholesterol in mRNA-Lipid Nanoparticles can be Replaced with the Synthetic Mycobacterial Monomycoloyl Glycerol Analogue MMG-1 - Lokras, Abhijeet G. ; 0000-0002-5617-0151; Baghel, Saahil S.; Jensen, Rune F.; Thakur, Aneesh; Franzyk, Henrik; Thofte, Oskar ; 0000-0002-4284-1006; Herrera-Barrera, Marco; Landry, Madeleine; Ongun, Melike; Tami, Ahmad; Thanthrige, Marlene P.; Callens, Eva; et al. (Advanced Functional Materials, 2025)
Messenger RNA (mRNA) vaccines based on lipid nanoparticles (LNPs) are stabilized with cholesterol, which is thought to be a critical LNP component because it is essential for membrane integrity and endosomal escape. Here, it is shown that cholesterol in LNPs can be replaced with an immunopotentiating lipid, i.e., a synthetic analogue of the C-type lectin receptor agonist monomycoloyl glycerol (MMG-1), without compromising physicochemical properties, in vivo transfection efficiency, and immunogenicity of the mRNA-loaded LNPs (mRNA-LNPs). Replacement of cholesterol with MMG-1 results in LNPs that mediate intracellular delivery of mRNA, which is translated into high levels of protein in vivo. Replacement of cholesterol with MMG-1 in LNPs improves the transfection efficiency in T cells, B cells, and macrophages in the spleen and lymph nodes of mice. In mice, MMG-1-based LNPs loaded with mRNA encoding the spike (S) protein of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) induce S-specific CD8+ T-cell responses and virus-neutralizing antibody responses, which are on par with the responses induced by cholesterol-based LNPs. Upon vaccination and a subsequent SARS-CoV-2 challenge of Syrian golden hamsters, replacement of cholesterol with MMG-1 in mRNA-LNPs enhances S-specific immunoglobulin G titers and reduces the SARS-CoV-2 load in the nasal cavity. These findings provide insights for improved design of LNPs for mRNA vaccine delivery.
Keywords: cholesterol; lipid nanoparticles; messenger RNA; monomycoloyl glycerol; SARS-CoV-2